The role of attention and emotion regulation in school readiness and school performance - Mittinty, M; Lynch, J; Sawyer, A; Chittleborough, C (My University, 2012)
Introduction: Understanding how the social and emotional development of young children influences academic outcomes is important to enable better targeting of interventions designed to improve school readiness and academic outcomes. This prospective study investigated the extent to which self-regulatory abilities when children were aged 2-3 years, including attention and emotion regulation, predicted academic outcomes at age 6-7 years. Method: The study used data from the birth cohort of the Longitudinal Study of Australian Children. Children were assessed when they were aged 2-3, 4-5 and 6-7 years (n=2230). Latent class analysis used items from the Strengths and Difficulties Questionnaire and the Short Temperament Scale to create indicators of attention and emotion regulation. School readiness at age 4-5 years was assessed using the child-completed ‘Who Am I?’ questionnaire. School performance at age 6-7 years was assessed with the teacher-rated Academic Rating Scale (ARS) and Approaches to Learning Scale (ALS). Preliminary results: Children with low emotion regulation at age 2-3 scored lower on school readiness (beta coefficient=-1.16, 95% CI -1.99 to -0.33) and school performance (ARS mathematical thinking beta coefficient-0.11, -0.19 to -0.02; ARS language and literacy beta coefficient=-0.16, -0.24 to -0.08; ALS beta coefficient=-0.24, -1.9 to -0.32) after adjustment for gender and socioeconomic disadvantage. Results were similar for attention regulation. Conclusion: Attention and emotion regulation in young children are potential targets for interventions designed to improve later school readiness and school performance. Key message: Children’s development of self-regulatory abilities in early life may play an important role in later success in school.
Keywords: Child Development -- Emotional; Education and Training -- School readiness; Education and Training -- Literacy and numeracy; Children -- Early childhood; Childhood and child development; Learning, education and training; Child Development; Children; Education and Training; Early childhood; Literacy and numeracy; Emotional; School readiness; Childhood and child development; Learning, education and training